PRESENCIA DE ESTRÉS LABORAL, SÃNDROME DE BURNOUT Y ENGAGEMENT EN PERSONAL DE ENFERMERÃA DEL HOSPITAL DEL NIÃ‘O MORELENSE Y SU RELACIÃ“N CON DETERMINADOS FACTORES LABORALES - Viejo, Sandra; Gonzalez, Margarita (European Scientific Journal, ESJ, 2013)
The nursing staff is one of the groups that are exposed to a lot of stressors as rotating shifts, working hours plaintiffs, amount and type of assistance to be provided to patients, as well as length of service and type of contract in that count, which can result in two types of response from individuals, known as Engagement positive, or a negative response in this case is work-related stress, and if this occurs chronically triggers the call Burnout Syndrome. This paper shows the results of the nursing staff of a public hospital in Mexico in terms of stressors to which they are exposed.